JUDICIAL LEGAL DEFENSE SYSTEMS: A COMPARATIVE STUDY ACROSS LEGAL TRADITIONS - Slinko, Dmytro; Alves, Fernando de Brito; Slinko, Sergey (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
This article provides a comprehensive comparative analysis of judicial systems of legal defense across various legal traditions, focusing on Europe and Brazil. It delves into the pivotal role of the bar in criminal proceedings, examining its organizational structure and operational dynamics. The study contrasts the French-English and Austrian-German bar systems, elucidating their distinct approaches to legal defense and courtroom representation. Moreover, the article explores how historical and cultural contexts shape procedural guarantees and the autonomy of legal representatives. It underscores the lawyer's critical role in upholding fair trial standards and safeguarding human rights, particularly through their involvement in evidence gathering and evaluation during criminal proceedings. The theoretical and practical insights presented contribute to a deeper understanding of legal defense mechanisms, paving the way for future research in judicial systems and human rights practices across diverse legal frameworks.